Ichthyofauna of streams of the Rio Sapucaí basin, upper Rio Paraná system, Minas Gerais, Brazil - Azevedo-Santos, Valter M.; Britski, Heraldo A.; Oliveira, Claudio; Benine, Ricardo C. (Biota Neotropica, 2019)
Abstract: The Rio Sapucaí basin, in Minas Gerais State, Brazil, is one of the many watersheds of the upper Rio Paraná system. Ichthyofauna surveys in this basin, in general, are scarce. In addition, small rivers and streams of the region have been targets of anthropogenic actions (e.g., pollution) - which suggest that more ichthyological studies must be performed within the watershed. In this study we provide a survey of species that occur within three streams of the lower Rio Sapucaí basin. Samples were collected in April, July, and November 2017 and in May 2018. Collections resulted in 349 individuals belonging to 28 species, five orders, and 12 families. Among our findings are three putatively undescribed species and the first record of Oligosarcus argenteus and Pareiorhina hyptiorhachis within the Rio Paraná system.